Sucrose metabolism: Anabaena sucrose-phosphate synthase and sucrose-phosphate phosphatase define minimal functional domains shuffled during evolution - Cumino, Andrea Carina (2002)
Based on the functional characterization of sucrose biosynthesis related proteins [SBP: sucrose-phosphate synthase (SPS), sucrose-phosphate phosphatase (SPP), and sucrose synthase (SuS)] in Anabaena sp. PCC7120 and sequence analysis, we have shown that SBP are restricted to cyanobacterium species and plants, and that they are multidomain proteins with modular architecture. Anabaena SPS, a minimal catalytic SPS unit, defines a glucosyltransferase domain present in all SPSs and SuSs. Similarly, Anabaena SPP defines a phosphohydrolase domain characteristic of all SPPs and some SPSs. Phylogenetic analysis points towards the evolution of modern cyanobacterial and plant SBP from a bidomainal common ancestral SPS-like gene.